Three Degree of Freedom Spatial Parallel Manipulator Inverse Kinematic Position Analysis - Rao Pundru, Srinivasa; Rao Nalluri, Mohan (International Journal of Engineering and Technology, 2018)
This paper presents inverse kinematic position analysis of three degree of freedom spatial parallel manipulator, which has three similar kinematic closed loops. Each loop consist of an actuated sliding linkage- rotational joint and spherical joint. The actuated sliding linkage is coupled to inclined limb of fixed base platform and rotational joints are integrated to the linear sliding actuators. The limbs are connected from rotational joints to moving platform by spherical joints. The degree of freedom of a manipulator is obtained by spatial kutzbach criterion. The inverse kinematic position analysis problem solved by using closed loop technique is applied to 3-coupled trigonometric equations which are obtained with side and behaviour constraints of a parallel manipulator. By using MATLAB the three non-linear coupled algebraic equations are solved. The inverse kinematic position analysis procedure is used in the development process of spatial parallel manipulator. The part of kinematic analysis is used to check the required positions-orientations and after kinematic process the obtained positions-orientations of the moving platform of the developed spatial parallel manipulator.Â Â